Japanese Listeners’ Judgments of Prolongations: With Focus on the Effect of Phonemic Length Contrast - Minji Kang; Inkie Chung; Jin Park (Audiology and Speech Research, 16(4), 2020)
Purpose: This study examined 1) what the absolute minimal duration of the lengthened Japanese sounds /s/, /ss/, /i/, and /i:/ are that are perceived to be abnormal by native speakers of Japanese; 2) what the relative ratio of a stimulus sound’s original length to its absolute perceptual threshold is; 3) whether differences are observed between short and long fricatives and between short and long vowels; and 4) whether phonemic length contrast affects the perceived abnormality of lengthened speech sounds. Methods: Twelve native speakers of Japanese (2 males, 10 females) listened to the Japanese sounds /s/, /ss/, /i/, and /i:/, each of which was lengthened by 0–400 ms in 20 ms increments. The participants rated whether the sound was normal (0) or abnormal (1). The minimal duration for each lengthened sound to be perceived as abnormal by the participants was calculated by analyzing the receiver operating characteristic curves using Youden’s index. Results: The minimal prolongation duration to be perceived as abnormal was 70 ms for /s/, 130 ms for /ss/, 70 ms for /i/, and 170 ms for /i:/. The percentage increases in duration required to be perceived as abnormal were 106% for /s/, 129% for /ss/, 117% for /i/, and 138% for /i:/. Conclusion: Phonemic length contrast affects the minimal prolongation duration and the percentage increase thresholds at which Japanese listeners perceive speech sounds as abnormally long. The implications of these results were further discussed within a diagnostic context of sound prolongation as one of core behaviors of stuttering. KCI Citation Count: 0